PRESUMPTION OF MOTHERHOOD ON CROSSROAD OF SURROGACY ARRANGEMENTS IN EU (EU and comparative law issues and challenges series (ECLIC), 2019)
The presumption “Mater semper certa est”, that is known from Roman law, indicates that the mother is always certain as she was traditionally seen as the progenitor and the one who had given birth. However, traditional view on motherhood is lately changing due to new procreation techniques that made the content of motherhood depended on contractual arrangements and opened the possibility to differentiate the progenitor from the person who has given birth. The surrogacy motherhood is considered as one of the new procreation techniques that made possible for single persons and couples with or without fertility problems to become parents. However, surrogacy motherhood made the notion of the mother interchangeable and depended on various arrangements between adults. It all represents a serious threat to various children’s rights including their right to know their origin and to be cared for by parents. Many Member States of the European Union (EU) realized the dangers of surrogacy arrangements and, in pursuit of the best interest of the child, enacted legislation to ban or restrict surrogacy. However, cross-border surrogacy arrangements, that are nowadays popular and untraceable, made possible to bypass those domestic legislations. The absence of any formal consensus within the EU on how to address the problem of cross-border surrogacy represents a serious threat to the protection of children’s rights.